La producción balletística de Martín y Soler en Rusia, a la luz de las últimas investigaciones - Fouter, Vera (Cuadernos de Música Iberoamericana, 2018)
This article examines the ballets Martín y Soler composed at the Russian Court. These previously unknown works have been studied by some interesting Russian musicological publications in recent years. Martín y Soler’s ballets and his relationship with major contemporary European choreographers are contextualised. The first catalogue of the ballets the Spanish composer premiered in Russia is proposed, analyzing some parameters of the scores that reflect the composer’s knowledge of contemporary opera production in Vienna, the city in which he had triumphed, and of works composers such as Gluck had premiered during the 1770s in Paris. Kriazheva and Maximovas’ studies reveal that the Valencian composer’s ballets are worthy of performance, as they maintain the high quality of the rest of his output.